PEMANFAATAN JENIS DAN KETINGGIAN PERANGKAP BERATRAKTAN MENGENDALIKAN WALANG SANGIT (Leptocorisa acuta) - Ameilia Zuliyanti Siregar; Annisa Ulfa; Lahmuddin Lubis (Jurnal AGROHITA: Jurnal Agroteknologi Fakultas Pertanian Universitas Muhammadiyah Tapanuli Selatan, 2020)
To find out the types and variations in the height of the traps that are effective in controlling stink bugs in rice, a synergistic study is needed. This research was conducted on paddy fields of ± 200 m2 at an altitude of ± 980 m above sea level (asl) in Tanjung Dolok Village, Marancar District, South Tapanuli Regency, starting from 9 October 2019 to 22 December 2019. Using Randomized Block Design (RAK) ) factorial with 3 treatment factors (crab carcass traps, prawn carcasses and golden snail carcasses) with a height variation with three replications so that a total of 16 combinations were carried out. The results showed that the types and interactions between the trap and the height of the trap were significantly different. while the treatment and replication factors had a significant effect. The best trap is to use a crab carcass trap with a height of 30 cm above the grain surface (A1P4) with a value of 90 individuals, a record average of 18.92 for six observations. When the effect of the type of trap on the number of stink bugs (Leptocorisa acuta) trapped has a very significant effect (F0.05 = 3.49). There is a correlation between the stink bug population and other insects with a significance value on the Pearson Correlation test of 0.794. Utilization of the type and height of traps with a variety of attractant carcasses is one of the Integrated Pest Management (IPM) which can be recommended for controlling the stink bug (L.acuta).